Proteomics in cancer research: Are we ready for clinical practice?. Issue 3 (December 2015) - Maes, Evelyne; Mertens, Inge; Valkenborg, Dirk; Pauwels, Patrick; Rolfo, Christian; Baggerman, Geert
Graphical abstract: Highlights: Oncoproteomics correlates better to the biological phenotype compared genomics and transcriptomics. With current progress in the field, mass spectrometry-based proteomics has major potential in both biomarker discovery and validation studies. Limited amount of clinical proteomics results are translated into a clinical setting due to major challenges. The nature and quality of clinical samples is of tremendous importance for proteomics experiments. Only proteomics studies with sufficient statistical power and an unbiased study design can deliver potential biomarkers. Analysis of a highly dynamic and complex proteome requires different fractionation strategies. Abstract: Although genomics has delivered major advances in cancer prognostics, treatment and diagnostics, it still only provides a static image of the situation. To study more dynamic molecular entities, proteomics has been introduced into the cancer research field more than a decade ago. Currently, however, the impact of clinical proteomics on patient management and clinical decision-making is low and the implementations of scientific results in the clinic appear to be scarce. The search for cancer-related biomarkers with proteomics however, has major potential to improve risk assessment, early detection, diagnosis, prognosis, treatment selection and monitoring. In this review, we provide an overview of the transition of oncoproteomics towards translational oncology. We describe which lessons are learned from currently approved protein biomarkers and previous proteomic studies, what the pitfalls and challenges are in clinical proteomics applications, and how proteomic research can be successfully translated into medical practice.